Tax Avoidance in F&B Companies in Relation Among Leverage, Sales Growth, and Firm Size with Profitability as Mediating - Kacaribu, Anton Adventus; Lombogia, Jennifer Valerie Carolinska (SAFE-Network, 2024)
The objective of this research is to examine how leverage, sales growth, and firm size have an effect on tax avoidance through profitability as mediating in food and beverage companies listed on the Indonesia Stock Exchange (IDX). The research utilizes three independent variables: leverage measured by Debt to Asset Ratio (DAR); sales growth measured by the change in current sales relative to previous sales; and firm size measured by the natural logarithm of total assets. The mediating variable is profitability, measured by Return on Assets (ROA), while the dependent variable is tax avoidance, measured by Cash Effective Tax Rate (CETR). The population of this research is all of the food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The purposive sampling method was used in determining the sample and there were 21 companies obtained with a total research sample of 84 obtained over four years. The results of this research show that leverage and sales growth partially have a significant effect on profitability, while firm size partially has no significant effect on profitability. Leverage, sales growth, firm size and profitability partially have no significant effect on tax avoidance.